Pengaruh Pemberian Inokulan Rhizobium sp dan Kompos Eceng Gondok (Eichhornia crassipes) terhadap Pertumbuhan dan Perkembangan Tanaman Kedelai (Glycine max) - Ayu Lestari Sarumpaet; Syawaluddin Syawaluddin; Rafiqah Amanda Lubis (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2018)
This study aims to determine the effect of Rhizobium sp inoculants and water hyacinth compost (Eichhornia crassipes) on the growth and development of soybean plants (Glycine max). The study used a factorial randomized block design. Each treatment was repeated three times. Treatment level 1 consists of; A0 (control), A1 (concentration 0.5gr) A2 (concentration 1gr), and A3 (concentration 2gr). The second level treatment consisted of K1 (3 gr/plant), K2 (5 gr/plant), K3 (7 gr/plant). The parameters observed were plant height (cm), number of leaves (strands), stem diameter (cm), number of fruits per plant (fruit). The results showed that the administration of Rhizobium sp inoculant and water hyacinth compost on soybean plants showed significant effect on all parameters observed, namely plant height, number of leaves (strands), stem diameter (cm) and number of pods per plant. Keywords: inoculant, rhizobium, compost, water hyacinth, soybean.